2016
DOI: 10.1016/j.jccw.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Placental Membranes for Management of Refractory Cutaneous Sinus Tracts of Surgical Origin: A Pilot Study

Abstract: Despite advances in surgical technique, postoperative complications may lead to refractory cutaneous sinus tracts or tunnels. Negative pressure wound therapy is difficult to apply in longer tracts with a narrow diameter opening and conservative treatment failures ultimately necessitate surgical revisions. The aim of this pilot study was a clinical utility assessment of two different commercial placental membrane products for refractory cutaneous sinus tracts of surgical origin. Patients were treated with viabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Clinical outcomes of vCPM have been reported in multiple studies for wounds of various etiologies and locations. [12][13][14][15][16][17][18][19][20] In the present study using vLPM adjunct to SOC, we demonstrated similar closure rates to those rates previously shown in clinical studies with the cryopreserved formulation (Fig. 2).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Clinical outcomes of vCPM have been reported in multiple studies for wounds of various etiologies and locations. [12][13][14][15][16][17][18][19][20] In the present study using vLPM adjunct to SOC, we demonstrated similar closure rates to those rates previously shown in clinical studies with the cryopreserved formulation (Fig. 2).…”
Section: Discussionsupporting
confidence: 87%
“…[8][9][10][11] High closure rates for difficult-to-treat wounds of different etiologies and locations have been demonstrated in multiple vCPM clinical studies. [12][13][14][15][16][17][18][19][20] Two prospective studies, one utilizing amnionderived vCPM and one utilizing chorion-derived vCPM, demonstrated a 62% and 59.3% closure rate for chronic diabetic foot ulcers (DFUs) and chronic complex DFUs, respectively. 12,14 Results of these DFU prospective clinical trials are mirrored by reported DFU closure rates in real-world patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on devitalized VCAM have demonstrated that viable cells are required for the tissue to respond in vitro in a wound-mimicking environment [ 18 , 45 , 46 ]. Clinical studies have demonstrated that VCAM results in a higher rate of wound closure in comparison to devitalized amnion-chorion for intractable large or sinus track wounds [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other VCAM retrospective and prospective clinical studies reported positive clinical outcomes in patients with acute and chronic wounds of various etiologies, and in a variety of surgical procedures [ 22 25 ]. Comparative effectiveness studies of VCAM versus a devitalized dehydrated amnion chorion product showed that the use of VCAM resulted in higher wound closure rate of larger, more difficult to treat wounds [ 26 , 27 ]. Clinical results are consistent with results from in vitro studies providing further support for preserving all components of native placental tissues.…”
Section: Introductionmentioning
confidence: 99%